Clinical features and treatment of patients with Vibrio vulnificus infection. (June 2017) - Yu, Wei; Shen, Xiaomin; Pan, Hongying; Xiao, Tingting; Shen, Ping; Xiao, Yonghong
Highlights: Some patients, especially male patients, who have acute sepsis, fever, cellulitis, and hemorrhagic skin bullae in the summer or autumn seasons, should be highly suspected of showing Vibrio vulnificus infections. Early diagnosis and surgical intervention are critical factors in attempts aimed at saving the patient's life. The in vitro study indicated that tigecycline alone might be a better potential therapeutic option than the traditional combination of doxycycline plus ceftazidime against V. vulnificus . Summary: Objectives: Infections with Vibrio vulnificus are commonly fatal, and the speed and accuracy of diagnosis and treatment is directly linked to mortality. The main aims of this study were to investigate the clinical characteristics of six patients with V. vulnificus infections retrospectively and to determine the effect of treatment with tigecycline (TGC) alone compared with doxycycline plus ceftazidime (DOX/CAZ). Methods: The medical records of patients were reviewed. The species-specific and pathogenic gene markers were detected by PCR, and multilocus sequence typing (MLST) was performed. Furthermore, the effects of TGC and of DOX/CAZ were determined using time–kill assays. Results: MLST revealed six different sequence types and five of them were novel. The complete clinical pattern ( vcg type C, CPS operon allele 1, 16S-rRNA type B ) was found in one strain and the others had a mixed pattern. The lesion was mainly located at the distal end of the extremities and the most common clinical symptoms were fever, pain, erythema, and local swelling. The in vitro time–kill assay indicated that TGC monotherapy at a concentration of 0.1 mg/l had a rapid bactericidal effect against the six tested V. vulnificus strains at 24 h. Conclusions: TGC alone might be a better potential therapeutic option than the traditional combination of DOX/CAZ against V. vulnificus .